Penyuluhan tentang PPh Pasal 21 pada Karyawan CV Rahmat - Rina Sulistyowati; Umar Yeni Suyanto; Rahma Jariatul Hajah Rizka (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
Tax is an important aspect of the Indonesian economy because it is one of the largest sources of state revenue, but the problem that many taxpayers are currently experiencing in fulfilling their obligations as taxpayers is limited knowledge of tax provisions, how to pay taxes and report SPT, especially on taxes. income. The Institut Teknologi dan Bisnis Ahmad Dahlan Lamongan community service team conducted this counseling to CV Rahmat employees with the aim of increasing tax awareness and compliance and channeling knowledge about taxation, especially regarding the PPh 21 reporting process, the results of this counseling really helped employees to calculate and report PPh 21 WP OP and understand more about the latest tax rules and regulations.